Answer:
13/18
Step-by-step explanation:
- 6.5 · 1/9 = 6 5/10 · 1/9
- 6 5/10 · 1/9 = 6 1/2 · 1/9
- 6 1/2 · 1/9 = 13/2 · 1/9
- 13/2 · 1/9 = 13/18
Therefore, 6.5 · 1/9 = 13/18.
it is 4/8
Step-by-step explanation:
because when you multiply 3 times 3 it equals 6
Y=Acos(p)+m, A=amplitude, p=period, m=midline, in this case:
A=1/2, p=360(t/12)=30t, m=(10-9)/2+9=9.5 so
h(t)=(1/2)cos(30t)+9.5
Answer: Apples come in bags of 4. Oranges come in bags of 6.
so it going to be Multiple 4x6=24 I explain it, is this how you want it
Step-by-step explanation: hope this help
Answer:
H0: µd = 0 (claim)
H1: µd ≠ 0
This is a two-tail t-test for µd
Step-by-step explanation:
This is a paired (dependent) sample test, with its hypothesis is written as :
H0: µd = 0
H1: µd ≠ 0
From the equality sign used in the hypothesis declaration, a not equal to ≠ sign in the alternative hypothesis is used for a two tailed t test
The data isn't attached, however bce the test statistic cannot be obtained. However, the test statistic formular for a paired sample is given as :
T = dbar / (Sd/√n)
dbar = mean of the difference ; Sd = standard deviation of the difference.